2022
DOI: 10.1098/rspb.2022.0330
|View full text |Cite
|
Sign up to set email alerts
|

Using genomic prediction to detect microevolutionary change of a quantitative trait

Abstract: Detecting microevolutionary responses to natural selection by observing temporal changes in individual breeding values is challenging. The collection of suitable datasets can take many years and disentangling the contributions of the environment and genetics to phenotypic change is not trivial. Furthermore, pedigree-based methods of obtaining individual breeding values have known biases. Here, we apply a genomic prediction approach to estimate breeding values of adult weight in a 35-year dataset of Soay sheep … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Few other studies have thus far sought evidence for micro-evolutionary change via shifts in GEBVs ( 16), though several studies in animals have examined shifts in predicted breeding values based on pedigrees (37). A recent study showed an increase in GEBVs calculated using genomic prediction algorithms for adult weight in a 35 year data set for Soay sheep which aligned with changes in predicted breeding values (from pedigree based studies), though phenotypic body weight decreased over this time span (15). In the present study, by contrast, we used the difference between predicted GEBV (based on relatedness) and observed GEBV (based on loci associated with the trait of interest) to infer that changes in allele frequency could be attributed to selection.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Few other studies have thus far sought evidence for micro-evolutionary change via shifts in GEBVs ( 16), though several studies in animals have examined shifts in predicted breeding values based on pedigrees (37). A recent study showed an increase in GEBVs calculated using genomic prediction algorithms for adult weight in a 35 year data set for Soay sheep which aligned with changes in predicted breeding values (from pedigree based studies), though phenotypic body weight decreased over this time span (15). In the present study, by contrast, we used the difference between predicted GEBV (based on relatedness) and observed GEBV (based on loci associated with the trait of interest) to infer that changes in allele frequency could be attributed to selection.…”
Section: Discussionmentioning
confidence: 90%
“…Few other studies have thus far sought evidence for micro-evolutionary change via shifts in GEBVs, though several studies in animals have examined shifts in predicted breeding values based on pedigrees 19 . A recent study showed a shift in GEBVs for adult weight in a 35 year data set for Soay sheep, though phenotypic body weight decreased over this time span 20 . Genomic prediction approaches have a wide future applicability in evolutionary studies 21 .…”
Section: Main Textmentioning
confidence: 92%
See 3 more Smart Citations